2018
DOI: 10.1177/1925362118782076
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Mitragynine-Associated Toxicity in Canada

Abstract: Mitragynine is amongst the more than 40 natural indole alkaloids derived from the Mitragyna speciosa, or kratom tree, also referred to as ketum. The compound is unique in that it exhibits dose-dependent clinical outcomes with stimulant effects at lower doses but sedative effects at higher concentrations. It is indigenous to Southeast Asia, where the local population has had extensive experiences utilizing the substance for its medicinal as well as recreational effects. Mitragynine is advertised as an herbal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In comparison to other reported mitragynine death cases, the age and gender, majority being male, were similar to what was previously found (5, 8 -17). For age of decedents in mitragynine-related deaths, Neerman et al (2013) reported the youngest decedent who was a 17-year-old male and the two oldest decedents were both female at 60 and 65 years old from Mata and Andera (2020) and Wang and Walker (2018), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison to other reported mitragynine death cases, the age and gender, majority being male, were similar to what was previously found (5, 8 -17). For age of decedents in mitragynine-related deaths, Neerman et al (2013) reported the youngest decedent who was a 17-year-old male and the two oldest decedents were both female at 60 and 65 years old from Mata and Andera (2020) and Wang and Walker (2018), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…PEA remains an unscheduled substance without restrictions on its inclusion in supplements. The patient had a measurable mitragynine concentration; however, the range of toxicity has not been well established, with deaths having been reported in association with postmortem concentrations of 1060 ng/mL and 2500 ng/mL [13].…”
Section: Discussionmentioning
confidence: 98%
“…An emergency case presenting with cardiorespiratory arrest could not be rescued despite the use of intralipid, that nevertheless improved somehow the conditions of a 26-year-old man, but proved ineffective in avoiding exitus, attributed to cardiorespiratory failure and hypoxic brain damage ( 91 ). A Canadian 56-year-old woman with chronic obstructive pulmonary disease, after skipping her medication and consuming kratom purchased from Indonesia, died due to respiratory failure ( 92 ). Her mitragynine levels in the femoral vein were found to be substantial but sublethal (under the reporting laboratory's threshold of fatality, which was 0.21 mg/L).…”
Section: Discussionmentioning
confidence: 99%